Analisis Financial Distres Pada Pt Matahari Departement Store Tbk - Yuliana Yuliana; Vitarin vitarin; aderina k harahap; Rina milyati (Universitas Bandar Lampung (UBL), 2021)
The phenomenon of shifting people's spending patterns is one of the factors affecting sales in modern retail. Retail companies that previously relied on physical stores, inevitably have to adjust the situation according to the current development of digital and online commerce. The purpose of this study was to determine whether PT Matahari Department Store Tbk experienced financial distress using the ohlson model. The research method used is to conduct quantitative descriptive analysis to describe, explain or summarize several circumstances, situations of an event or various research variables according to the event as it is by using quantitative data, namely data in the form of numbers or qualitative data. which is extrapolated from the ratio. finance using equations in the ohlson model. The results showed that PT Matahari Department Store did not experience financial distress